The Political Discovery of the Life in Hannah Arendt and Michel Foucault - Daniel Toscano López (Revista de Filosofia, 2016)
In this article I propose to analyze the link between two unlike authors both in the method and in the object of his investigations (arendt and Foucault). The above mentioned link centres that both approach the problem of the administration of the life, in such a way that I will emphasize that both in arendt and in Foucault there is implicit the “political discovery of the life”. To account for this, this reflection is structured in three stages: I first outline the problem of “biopolitics” within modernity also propose the main arguments in arendt and Foucault lead to «political discovery of the life»; after I expose, without pretending to exhaust them, some affinities between both authors face the issue of “biopolitics”; finally, and thirdly, pointed strategies that French thinker like German-Jewish thinker display face increasing life management: «the aesthetics of existence» and «political singling».